Schizoanalysis, Marginalism, Fourierism (on two additional resources for understanding the economic views of Deleuze and Guattari) - Pogrebnyak, Alexander (Stasis, 2019)
This article analyzes how two theories, both emerging in the nineteenth century—Fourierism and marginalism—influenced the economic views of Gilles Deleuze and Félix Guattari. Despite the fact that explicit recourse to those theories in Capitalism and Schizophreniais merely sporadic, the implicitly inherent interrelation between these ideas and a schizoanalyst view of economics turns out to be rather substantial. First, marginalism is concerned with a “logic of the (pen)ultimate,” within the framework of which a distinction between a limit and a threshold is introduced. This distinction is important for understanding how the “apparatuses of capture,” which subjugate desiring-production to the despotic, and later to the capitalist regime, function. Second, Fourier’s “gigantism,” mentioned by Deleuze and Guattari, turns out to be an anticipation of their own theory of the “desiring machine” synthesis not only as to its general intention, but also as a detailed social mechanics, built upon the engagement of “distributive passions.”